LICENCIAMENTO AMBIENTAL DE OBRAS PÚBLICAS NO BRASIL - Magalhães, Maximiliano; Hippert, Maria Aparecida (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The environmental licensing is an important environment management tool, it helps to control enterprises and activities that generate impacts on the environment looking after the sustainable development. In Brazil, it is a responsibility of the entities that make up the National Environmental System SISNAMA, used as an administrative procedure, subdivided into three phases, which may result in the issuance of up to three licenses: Pre Licensing - LP, Installation - LI and Operation - LO. In process at the Federal Senate is the Federal Constitutional Amendment Bill - PEC 65/2012, that proposes changing the way environmental licensing is done, saying that the approval of the Environmental Impact Assessment will be enough for the process, thus simplifying and altering the environmental licensing process currently in force in Brazil. The objective of this study is to discuss the importance of the environmental licensing in light of the changes in legislation proposed by the Federal Senate. It consists of the current legislation applicable to environmental licensing in Brazil, drawing a correlation with the proposal PEC 65/2012 currently at the Federal Senate, showing that environmental licensing process has an important function of monitoring and pointing out measures to mitigate the environmental impacts.